Is digital transformation profitable for banks? Evidence from Europe - Citterio, Alberto; King, Timothy; Locatelli, Rossella (Elsevier, 2024)
Studies on the impact of digital transformation (DT) on bank performance are typically restricted to single countries and present mixed findings. Using data on 279 EU-27 banks from 2017 to 2022 and employing a novel DT index, we demonstrate that DT is associated with higher bank profitability, and that IT and network efficiency are key drivers. Furthermore, Covid-19 and the level of country IT positively moderate this relationship. Interestingly, additional analyses also reveal nonlinear relationships, which suggest that profitability gains from DT investments can take time to materialize and that there are diminishing marginal returns to some DT investments.
Keywords: Digital transformation; IT adoption; Digital channels; bank performance; COVID-19; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|